2018
DOI: 10.1111/jog.13597
|View full text |Cite
|
Sign up to set email alerts
|

Infertility treatment strategy involving combined freeze‐all embryos and single vitrified‐warmed embryo transfer during hormonal replacement cycle for in vitro fertilization of women with hypogonadotropic hypogonadism

Abstract: Our results demonstrated that IVF followed by single vitrified-warmed ET in adjusted endocrine milieu during the HR cycle is an effective fertility treatment for women with HH and decreases the incidence of complications, including multiple conceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Kuroda et al. ( 21 ) reported good clinical pregnancy and live birth rates (65.1% and 50.5%) after FET in patients with HH; however, they did not compare these outcomes with a control population or with fresh embryo transfer cycle outcomes. Our results suggest that patients with HH have lower pregnancy rates with FET than those with fresh transfer when controlling for confounders and those with PCOS or tubal factor infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Kuroda et al. ( 21 ) reported good clinical pregnancy and live birth rates (65.1% and 50.5%) after FET in patients with HH; however, they did not compare these outcomes with a control population or with fresh embryo transfer cycle outcomes. Our results suggest that patients with HH have lower pregnancy rates with FET than those with fresh transfer when controlling for confounders and those with PCOS or tubal factor infertility.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study showed similar cumulative pregnancy and live birth rates after single and double frozen-thawed blastocyst transfers after a freezeonly strategy, 20 and another study evaluating the freeze-only strategy and SET in women with hypogonadotropic hypogonadism showed that SET is an effective strategy for decreasing the incidence of multiple conceptions while maintaining satisfactory live birth rates (50.5%). 21 Corroborating our hypothesis of better clinical outcomes after a freeze-only strategy plus SET, the American Society for Reproductive Medicine and the Society for Assisted Reproductive Technology (ASRM/SART) recommended SET for patients with a good prognosis aged < 38 years, except in cases in which the patient had several previous cycle failures and for whom DET was suggested. 5 Reinforcing the efficiency of the ASRM/SART recommendation, Eubanks et al 22 evaluated retrospective data about clinical PRs before and after the ASRM/SART guidelines were published in 2017, as their clinic policy is to transfer no more than the recommended number of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study showed similar cumulative pregnancy and live birth rates after single and double frozen-thawed blastocyst transfers after a freeze-only strategy, 20 and another study evaluating the freeze-only strategy and SET in women with hypogonadotropic hypogonadism showed that SET is an effective strategy for decreasing the incidence of multiple conceptions while maintaining satisfactory live birth rates (50.5%). 21 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, eight were fresh, and two were frozen-thawed ET cycles, and one was a combination of both. Recently, Kuroda et al reported that a combination of freeze-all embryo and single vitrified-warmed ET with a hormone replacement cycle for HH, including IHH, had good cumulative pregnancy rates of 73.4% in up to 3 ET cycles 30) . Seven retrospective cohort studies comparing IHH with tubal or male infertility and other causes of poor ovarian responsiveness to gonadotropins have been reported 23 - 27 , 29 , 31) .…”
Section: Discussionmentioning
confidence: 99%